Exfiltrating data from Android devices. Issue 48 (February 2015) - Do, Quang; Martini, Ben; Choo, Kim-Kwang Raymond
Abstract: Modern mobile devices have security capabilities built into the native operating system, which are generally designed to ensure the security of personal or corporate data stored on the device, both at rest and in transit. In recent times, there has been interest from researchers and governments in securing as well as exfiltrating data stored on such devices (e.g. the high profile PRISM program involving the US Government). In this paper, we propose an adversary model for Android covert data exfiltration, and demonstrate how it can be used to construct a mobile data exfiltration technique (MDET) to covertly exfiltrate data from Android devices. Two proof-of-concepts were implemented to demonstrate the feasibility of exfiltrating data via SMS and inaudible audio transmission using standard mobile devices. Graphical abstract: Highlights: Adversary model for Android covert data exfiltration. Mobile data exfiltration technique (MDET). Inaudible data exfiltration.